2015
DOI: 10.1007/s13595-015-0504-7
|View full text |Cite
|
Sign up to set email alerts
|

Xylem and soil CO2 fluxes in a Quercus pyrenaica Willd. coppice: root respiration increases with clonal size

Abstract: Abstract• Key message Xylem and soil CO 2 fluxes in coppiced oak forests increase with clonal size, suggesting larger expenditures of energy for root respiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…deltoides plantation, F T at the stem base even doubled the amount of soil CO 2 efflux originated from root respiration (Aubrey & Teskey, ). Likewise, substantial xylem [CO 2 ] variability observed at the stem base of Platanus occidentalis trees was associated to stem size with potentially bigger roots (Teskey & McGuire, ), and F T at the stem base scaled up with soil CO 2 efflux in multistemmed oak trees with larger root systems (Salomón et al, ). Here, higher xylem [CO 2 ] measured closer to the soil level suggests greater root respiration in eCO 2 rings.…”
Section: Discussionmentioning
confidence: 99%
“…deltoides plantation, F T at the stem base even doubled the amount of soil CO 2 efflux originated from root respiration (Aubrey & Teskey, ). Likewise, substantial xylem [CO 2 ] variability observed at the stem base of Platanus occidentalis trees was associated to stem size with potentially bigger roots (Teskey & McGuire, ), and F T at the stem base scaled up with soil CO 2 efflux in multistemmed oak trees with larger root systems (Salomón et al, ). Here, higher xylem [CO 2 ] measured closer to the soil level suggests greater root respiration in eCO 2 rings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the microbial respiration could increase around vigorous trees as a result of higher root exudation rates and leaf and fine root litter supply to the soil [14]. In support of this reasoning it has been observed that variables related with photosynthetic C uptake, such as the leaf area index, sap flow, tree size, or tree proximity to and live tree basal area around R s sampling locations are positively related to R s [11,[15][16][17][18][19][20]. Nevertheless, R s can be relatively homeostatic across successional stages or after perturbations [8,[21][22][23].…”
Section: Introductionmentioning
confidence: 83%
“…Stem CO 2 flux is typically composed of respiration from the stem. However, it has been found that passive diffusion of CO 2 out of the stem from water in the xylem that is being transported from the roots to the shoots, can contribute to the stem CO 2 flux as well [48]. The CO 2 concentration in the soil pores is high, typically several thousand ppm, which leads to CO 2 being dissolved in the soil water [49][50][51].…”
Section: Overall δ 13 C Values Of the Co 2 Fluxes From Intact Soils mentioning
confidence: 99%